The dragons, the giant, the women a memoir - Moore, Wayétu (Minneapolis, Minnesota Graywolf Press, 2021)
When Wayétu Moore turns five in Monrovia, Liberia, all she can think about is how much she misses her mother, who is working and studying in New York. Before she gets the reunion her father promised, war breaks out in Liberia, and her family is forced to flee their home, walking and hiding for weeks until they arrive in the village of Lai. Finally a rebel soldier smuggles them across the border to Sierra Leone, reuniting the family and setting them off on another journey, this time to the United States. Spanning this harrowing time in Moore's early childhood, her years adjusting to life in Texas as a Black woman and an immigrant, and her eventual return to Liberia, The Dragons, the Giant, the Women is a deeply moving story of the search for home in the midst of upheaval. Moore shines a light on the great political and personal forces that continue to affect migrants around the world, and calls on us to acknowledge the tenacious power of love and family
Keywords: Childhood and youth